SPATIAL ARRANGEMENTS IN TRADITIONAL M'ZABITE HOUSES (Sciences & Technology. A, exactes sciences, 2003)
This paper aims to study the morphology of M'zabite traditional houses. The study uses the space syntax method. Space syntax proposes a fundamental relationship between the configuration of space in a house and the way that it functions. It is the aim of this research work to test this proposition in an M'zab cross settlement sample. The study particularly focuses on the measure known as " difference factor ". The concept of difference factor has been widely used as a technique to measure the strength of a spatial genotype. As a preliminary conclusion, four characteristic patterns of integration are found, the first one centred on the Ammas N'tadart  [Berber for Wast Eddar], the second on the Ikoumar or arched portico, the third on the stairs, and the last but not the least, is centred on the Tigharghart or upper courtyard.